Pemisahan Itrium dengan Cara Ekstraksi Menggunakan Solven TOPO - Handini, Tri; Sukarna, I Made; Yuniyanti, Anisa Dwi (EKSPLORIUM, 2018)
Separation process of yttrium by extraction using TOPO solvents has been done. The purpose of this study is to find out the optimum condition of the variation effect of extractant concentration, stirring time, and acidity of the rare earth feed and to determine the distribution coefficient, separation factor, and extraction efficiency (%), using the liquid-liquid extraction method. The feed used were rare earth elements of xenotime sand. The extractant used in the research were TOPO (tri-n-octylphosphine oxide). Concentration of yttrium (Y), disprosium (Dy), and gadolinium (Gd) were determined using X-ray fluorescene spectrometer. Optimum conditions of the extraction process obtained from this study were: TOPO extractant concentration in kerosene 20%, stirring time 15 minutes, acidity of feed 0.5 M. Obtained value of distribution coefficient Y = 5.61; Dy = 2.06; Gd = 0.99. For extraction efficiency Y = 85.13%, Dy = 67.80%, Gd = 50.17% whereas separation factor Y-Dy = 2.7186 and Y-Gd = 5.6861.